Educación y Personas Mayores en contexto de pandemia. Desigualdades vigentes - Martínez, Verónica Natalia (Universidad Nacional de Villa María, 2021)
The article proposes to develop some conceptual elements of educational and extension public policies in the Argentine context, located in the experience of the National University of Villa María in the gerontological field. In this case, we speak of the University Extension Program for Older Adults (PEUAM) belonging to the Extension Institute of the National University of Villa María (UNVM), which, after twenty years of execution, faced with the effects of the pandemic due to COVID 19, faces the question of how to think about possible strategies around the diversities and inequalities that “staying at home” goes through for the elderly. The development of the text incorporates the human rights approach, establishing relationships between aging processes, the social construction of old age within the framework of preventive and mandatory social distancing and the consequent implementation of virtual proposals, taking into account that the move from a face-to-face program to virtuality requires interventions that allow the inclusion of older people, creating a space for learning and social, cultural and educational exchange, in order to fulfill the mission of university extension.